Pendekatan VECM : Kemiskinan di Kabupaten Mandailing Natal - Amnah Faridah Hasibuan; Khairina Tambunan; Imsar Imsar (Institut Teknologi dan Bisnis (ITB) Semarang, 2026)
This study aims to analyze the effect of the Open Unemployment Rate (OUR), Human Development Index (HDI), and zakat on poverty in Mandailing Natal Regency. The study employed a quantitative approach using the Vector Error Correction Model (VECM) based on quarterly secondary data from 2015 to 2025. The analytical procedures included stationarity testing, optimal lag selection, Johansen cointegration testing, VECM estimation, Granger causality testing, as well as Impulse Response Function (IRF) and Variance Decomposition (VD) analyses. The findings indicate that all variables were stationary at the second difference level, with an optimal lag length of four, and exhibited a long-run cointegration relationship. The VECM estimation reveals that, in the long run, the Open Unemployment Rate has a positive and significant effect on poverty, while zakat has a negative and significant effect in reducing poverty. In contrast, the Human Development Index does not significantly affect poverty, which may be explained by the presence of a development time lag and employment mismatch between workforce competencies and labor market demands. The Granger causality test indicates a one-way causal relationship from the Open Unemployment Rate to the Human Development Index. Furthermore, the Variance Decomposition analysis shows that poverty variation is predominantly explained by its own shocks (96.25%), reflecting the persistence of structural poverty. Therefore, policy synergy through employment expansion and the optimization of productive zakat programs based on business empowerment is recommended to accelerate poverty alleviation in Mandailing Natal Regency.